PERAN KEPERCAYAAN MEMEDIASI PENGETAHUAN DENGAN PARTISIPASI PENGGUNA TOKO ONLINE DI KOTA DENPASAR - Yunita Sari, Made Dhena; Sukaatmadja, I Putu Gde; Yasa, Ni Nyoman Kerti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Increasingly rapid development of the internet has made major contributions to its user especially in online transaction. Although online transaction has a high risk, yet its also increase. The enhancement of user online transaction related to trust and knowledge user. This research was aimed to identify the role of trust in mediating knowledge toward online shop user participation in Denpasar city. The populations in this research were all internet user’s ever online transaction in Denpasar. The method of sample determination is purposive sampling, the total numbers of sample were 185 people. The research hypothesis test used Structural Equation Modeling (SEM) and Sobel Test. The results were knowledge has directly positif effect and significant to trust of online transaction  user; knowledge has directly positif effect and significant to participation; trust has directly positif effect and significant to participation ; trust has significant partial mediating knowledge effect to user online shop participation. In this research help business owner for increasing trust of online shop customers  for example focus on safety and satisfaction of transaction and educate customers for online shop participation.
Keywords: online transaction, trust, knowledge, participation